52.4k views
4 votes
2(x-3)+9=5+x-1 plz help me I am confused

2 Answers

4 votes

Answer:

2(x-3)+9+5+x-1 is the anomaly for every answered question

x = 1

Explanation:

did you get this question from canvas?

User Kalib Zen
by
4.5k points
3 votes

Answer:

x = 1

Explanation:

Lets start working through this problem!

2(x-3) + 9 = 5 + x - 1

Lets get rid of the parenthesis

2x - 6 + 9 = 5 + x - 1

Now lets combine like terms

2x + 3 = 4 + x

Now lets move the x to the other side

x + 3 = 4

Now lets move the 3 to the other side

x = 1

And now we are done!

User Leonardorame
by
5.0k points